2022
DOI: 10.1097/mop.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Puff bars: a dangerous trend in adolescent disposable e-cigarette use

Abstract: Purpose of review Puff Bars, a brand of disposable e-cigarettes, have skyrocketed in popularity recently, presenting significant health and safety risks to adolescents. Puff Bars and other disposable e-cigarette products are attractive to children and teenagers because of their vibrant colors and flavors, low cost, and ease of access. This review examines the rise in Puff Bar popularity, describes notable health and safety concerns, and provides advice for parents and pediatricians in identifying and preventin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In fact, the makers of the most popular products among youth, such as JUUL, have a well-documented record of advertising to youth 23. While recently JUUL has complied with FDA directives and has voluntarily pulled many of its flavoured products (such as Mango, Fruit, Cucumber and Creme products) off the market in November 2018,24 there remains considerable ongoing concern with the burgeoning youth-oriented market for flavoured disposable products, such as Puff Bar 25…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the makers of the most popular products among youth, such as JUUL, have a well-documented record of advertising to youth 23. While recently JUUL has complied with FDA directives and has voluntarily pulled many of its flavoured products (such as Mango, Fruit, Cucumber and Creme products) off the market in November 2018,24 there remains considerable ongoing concern with the burgeoning youth-oriented market for flavoured disposable products, such as Puff Bar 25…”
Section: Discussionmentioning
confidence: 99%
“…New research papers continued to be published throughout 2022 with no mention of THC vapes as the source of Vitamin E acetate [13] or falsely claiming that specific brands of e‐cigarettes cause EVALI [14]. This demonstrates that, in addition to the public, clinicians and researchers continue to be confused by the name EVALI.…”
Section: E‐cigarette or Vaping Product Use‐associated Lung Injury (Ev...mentioning
confidence: 99%
“…A 2022 study led in France 6 showed that 13% of 13-16 year olds had already tried a DEC. The popularity of this product among youth could be partially explained by their presence on social media 7 and targeted marketing. 8 In addition to environmental issues and questions about the association between e-cigs WHAT IS ALREADY KNOWN ON THIS TOPIC ⇒ New disposable electronic cigarettes (DEC) are attracting youth with fruity and sweety flavours and bright colours.…”
Section: Introductionmentioning
confidence: 99%